Ativação muscular e parâmetros espaço-temporais da iniciação de marcha em idosas com e sem história de quedas recorrentes - Andrea de Jesus Lopes (2009)
Gait initiation (GI), a transition phase between standing and walking, requires effective force reaction to the maintenance of the dynamic equilibrium. Elderly fallers may not be able to develop muscular and effective postural strategies to enhance stability during GI and therefore protect them against recurrent falls. Therefore, the objective of this study was to compare the spatial and temporal parameters and the muscular pattern of soleus (SOL), gastrocnemius (GAS) and tibialis anterior (TA)muscles during GI in two groups of elderly individuals with and without history of recurrent falls. Eighty-five community-dwelling elderly females, 60 years older or more, participated in the study. The volunteers were divided in two groups, with and without history of falls, according to the occurrence of 2 or more falls in the previous year. Spatial and temporal parameters during GI were recorded during self selected walking velocity using an electronic carpet with internal sensors, the GAITRite® system. For temporal activation of the SOL, GAS and TA muscles the EMG BIOPAC® system was used. The recurrent faller group comprised 33 elderly females (73.8 ± 5.4 years) and the non-faller group 52 elderly females (70.9 ± 5.6 years). The faller group was statistically older (p=0,008) and had an average more falls (4.1±8.3 x 0,2±0,4) in the last year when compared to the non-faller group. A Multivariate Analyses of Variance (MANOVA) was conducted with the dependent variables base of support, time, normalized velocity (normalized by the length of the legs) and step length of the first step during GI, considering as independent variable group (fallers and non-fallers). The Wilkss lambda criterion was significant = 0.88, c2 (1,N=82)= 15.352, p< .00, indicating that the dependent variables were significantly affected by the main effect group. A simultaneous discriminant analysis was conducted to determine which dependent variable could predict the condition group (recurrent faller and non-faller). The results showed that normalized velocity and base of support of the first step during GI could discriminate the condition groupwith 60.7% of the cases classified correctly. The correlation between the predictors demonstrated the strongest correlation of the normalized velocity variable with the discriminant function when compared to base of support of the first step (r=0.88 and 0.62, respectively). Regarding the temporal activation data, latency and total time activation of the SOL GAS and TA muscles, the results showed no significant difference between groups during GI. In conclusion, female elderly with recurrent falls decrease their velocity as an attempt to enhance stability during GI. Thedecrease in the base of support could be a result of deficit in the postural control present in the elderly fallers group.